(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article analyzes the issues of intellect and being, their interaction, the essence of man, his role in the perception of the essence of being, the factors and sources that determine the ontological structure and functional existence of an individual. The level of socio-economic development of society, the ideological and ideological environment, the essence of the policy pursued by the state, the content and form of the educational system determine the ontological structure and functional existence of the individual. Trends in the historical development of society are manifested in individual potential. The level of socio-economic development of society, the ideological and ideological environment, the essence of the policy pursued by the state, the content and form of the educational system determine the ontological structure and functional existence of the individual. Trends in the historical development of society are manifested in individual potential. The human mind is constantly developing on the basis of Learning, Mastering the various knowledge created by mankind. In order to further develop the mind, a person needs the right-thinking dormitory. To do this, Akli should rely on methods of cognition, in particular logical cognition. But it is of great importance that the quality of knowledge, advanced ideas and knowledge acquired by the individual in the bunda. Thus, the question of existence is the negation of all the issues that a person faced during his first attempts to understand the world wisely. The existence or nonexistence of certain things immediately took place from the centre of his attention, as soon as a person began to philosophical reasoning.